MAIN METHODS AND APPROACHES USED IN LEARNING A FOREIGN LANGUAGE (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article examines the main methods and approaches used in foreign language learning from a theoretical and pedagogical perspective. It analyzes such methodologies as the Grammar-Translation Method, the Direct Method, the Audiolingual Method, the Communicative Approach, as well as modern interactive and technology-based teaching strategies. Special attention is given to the pedagogical foundations, advantages and disadvantages of each method, and their role in developing learners’ communicative competence. The study also highlights the importance of an integrative approach and the application of innovative educational technologies in contemporary foreign language instruction. The findings demonstrate that the effective combination of various teaching methods significantly enhances language learning outcomes.